Pengaruh Good Corporate Governance dan Kinerja Keuangan Terhadap Enterprise Risk Management - Ikhwani Zulaikha; Murtanto Murtanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the effect of good corporate governance and finansial performance on enterprise risk management in food & beverage companies listed on the Indonesia Stock Exchange. The type of research in this research is causal research using secondary data and quantitative types. The population in this study are food & beverage companies in 2018-2021. The sample selection methode use purposive sampling, namely the sampling methods was based on certain criteria set by the researcher is an objective. Based on this method obtained 29 companies and obtained total samples (29 x 4 years) are 116. The hypothesis test used is Multiple Linier Regression Analysis. The result show that board of commissioners independent, board of directors and ROE have a positive significant effect on enterprise risk management.